The N-Methyl-D-Aspartate Receptor Antagonist Dextromethorphan Improves Glucose Homeostasis and Preserves Pancreatic Islets in NOD Mice - Wörmeyer, Laura; Nortmann, Oliver; Hamacher, Anna; Uhlemeyer, Celina; Belgardt, Bengt; Eberhard, Daniel; Mayatepek, Ertan; Meissner, Thomas; Lammert, Eckhard; Welters, Alena (Hormone and Metabolic Research, 2024)
For treatment of type 1 diabetes mellitus, a combination of immune-based interventions and medication to promote beta-cell survival and proliferation has been proposed. Dextromethorphan (DXM) is an N-methyl-D-aspartate receptor antagonist with a good safety profile, and to date, preclinical and clinical evidence for blood glucose-lowering and islet-cell-protective effects of DXM have only been provided for animals and individuals with type 2 diabetes mellitus. Here, we assessed the potential anti-diabetic effects of DXM in the non-obese diabetic mouse model of type 1 diabetes. More specifically, we showed that DXM treatment led to five-fold higher numbers of pancreatic islets and more than two-fold larger alpha- and beta-cell areas compared to untreated mice. Further, DXM treatment improved glucose homeostasis and reduced diabetes incidence by 50%. Our data highlight DXM as a novel candidate for adjunct treatment of preclinical or recent-onset type 1 diabetes.
Keywords: type 1 diabetes; islet cell protection; islet inflammation; beta cells; diabetes